Assistance in Implementing Internal Controls for the Sales and Accounts Receivable Cycle to Support Business Sustainability at MSME Garasi GA in Gowa Regency - Wahyuni; Masrullah; Armansyah Hilman; Muh Syamrialdi F.S; Muhammad Yasser; Asrar Abukair; Anugrah Ramadhan; Sudirman (www.amertainstitute.com, 2026)
Reliable financial recording is a fundamental requirement for improving the sustainability and competitiveness of Micro, Small, and Medium Enterprises (MSMEs). However, many MSMEs continue to experience difficulties in maintaining proper accounting records because of limited financial literacy, inadequate bookkeeping systems, and the absence of standardized financial reporting practices. This community engagement project aimed to assist Garasi GA MSME in Gowa Regency in implementing an accounting cycle and strengthening internal control over sales and accounts receivable based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The program employed a participatory mentoring approach involving field observation, problem identification, accounting training, direct technical assistance, evaluation, and post-implementation monitoring. Data were collected through interviews, direct observations, and documentation of financial transactions. The findings revealed that the enterprise initially lacked formal accounting records, general journals, ledgers, receivables administration, and financial statements, resulting in weak financial control and limited managerial decision-making. Following the mentoring program, the MSME successfully established a chart of accounts, general journals, ledgers, accounts receivable records with aging schedules, income statements, and statements of financial position in accordance with SAK EMKM. Furthermore, improvements were observed in transaction documentation, separation of business and personal finances, and monitoring of outstanding receivables, thereby strengthening key components of the COSO internal control framework. These outcomes demonstrate that practical accounting assistance effectively enhances financial governance, internal control effectiveness, and business sustainability while providing a replicable model for improving accounting practices among Indonesian MSMEs through university-community collaboration.